Bathing Jewish, Bathing Greek: Developing an Approach to De-Categorising Hellenism and Judaism - Scales, Joseph (Palestine exploration quarterly, 2022)
Recent works on the categorisation of ancient Judaism have begun to call into question the division between Judaism and Hellenism, often reified as two distinct cultural spheres, even as scholars seek to explain texts and artefacts which show elements traditionally ascribed either to Judaism or Hellenism. These theoretical formulations have made some impact in the discussion of ancient Jewish texts but have so far failed to be fully appreciated in archaeological and architectural scholarship. This article will present the Magdala bathhouse (Galilee) as an example which forces us to re-evaluate the construction of Judaism and Hellenism. It proposes that we should view Judaism as an integral part of Hellenism, and any cultural output of ancient Judaism should be interpreted as a full participant in any definition of Hellenism.